Dual consumer–organisation identification in international alliances and partnerships: consumers' supportive intentions towards local and foreign firms. (3rd October 2018) - Wilkins, Stephen; Butt, Muhammad Mohsin; Heffernan, Troy
Abstract: This study investigates whether firms that are evaluating potential partners might benefit from considering how consumers view these organisations, specifically the extent to which consumer identification with local and foreign partners influences consumer satisfaction with a co-branded product and consumers' post purchase/consumption supportive intentions towards each partner. Data came from institutions of higher education in Hong Kong and Sri Lanka that operate in collaboration with a foreign partner. A conceptual model was developed and then tested using structural equation modelling. Dual consumer–organisation identification was found to be a significant predictor of consumer satisfaction with the co-branded product and consumers' supportive intentions towards each partner. Furthermore, the perceived identity attractiveness of each partner was significantly related to the consumers' identification with each partner. The results suggest that organisations which indulge in collaborative arrangements with foreign firms should recognise that each partner plays a significant and distinct role in generating consumer satisfaction and positive post-purchase/consumption behaviours.